BLAP-Tags, TUBEs and DUB-Chips: Combined Novel Technologies will Advance Molecular Epithelial Physiology - Hamilton, Kirk L. (Frontiers in Physiology, 2012)
The field of ubiquitylation and dubiquitylation of proteins in molecular physiology is growing at a rapid rate. Our understanding of molecular physiology of these processes may become limited by the advancement of technologies that scientists can employ. Therefore, it is important to approach physiological questions of ubiquitylation and dubiquitylation of proteins from a multiple methodological direction. Indeed, the role of ubiquitylation and dubiquitylation of proteins in cellular function has been implicated in the pathophysiology of human diseases including cancer, viral diseases and neurodegenerative disorders. There are many modulators (activators and inhibitors) of ubiquitylation and dubiquitylation. Therefore, the link is being able to rapidly assess potential modulators of ubiquitylation and dubiquitylation and determine which specific modulators play a role(s) within a particular physiological setting. After the specific modulators have been identified, further experimentation is required to assess the downstream use as potential clinical target for a particular disease. The first step is to identify the specific modulators. This perspective highlights a multi-prong technologies approach that uses three novel techn